2014
DOI: 10.1044/2014_aja-13-0037
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Hyperacusis and Future Directions: Part II. Measurement, Mechanisms, and Treatment

Abstract: Hyperacusis can make life difficult in this increasingly noisy world, forcing sufferers to dramatically alter their work and social habits. We believe this is an opportune time to explore approaches to better understand and treat hyperacusis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
78
0
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 176 publications
(138 reference statements)
1
78
0
15
Order By: Relevance
“…Regarding comorbidity, we found that hyperacusis co-occurred with several diagnoses, similar to other studies including psychiatric diagnoses,[15373839] functional somatic syndromes,[1423242526] hearing impairment,[40] and tinnitus. [7161718]…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Regarding comorbidity, we found that hyperacusis co-occurred with several diagnoses, similar to other studies including psychiatric diagnoses,[15373839] functional somatic syndromes,[1423242526] hearing impairment,[40] and tinnitus. [7161718]…”
Section: Discussionsupporting
confidence: 87%
“…[4121314] To what extent individuals with hyperacusis in the general population cope with their condition by seeking medical attention lacks documentation to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Intense sounds are not only perceived as painfully loud (Ades et al, 1959), but can also induce pain sensations in around the external ear (otalgia; Dominguez et al, 2006; Hebert et al, 2013; Henry et al, 2014; Kaltenbach et al, 2000; Knipper et al, 2013; McFerran and Baguley, 2007; Norena, 2011; Pienkowski et al, 2014; Tyler et al, 2014a; Van Campen et al, 1999; Westcott et al, 2013). Pain transmitting neuropeptides and receptors are present in the CN and auditory nerve (Aguilar et al, 2004; Bauer et al, 2007b; Jongkamonwiwat et al, 2003; Nguyen et al, 2014; Phansuwan-Pujito et al, 2003; Tongjaroenbuangam et al, 2006), raising the possibility that loud sounds may trigger the perception of pain through these signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperacusis is a comorbidity in 80% of tinnitus patients (4) suggesting common pathogenic mechanisms (5). In the most severe cases, hyperacusis is described as debilitating "ear pain" (6). The response to trauma by type II afferents may relate most directly to such noxious hearing-"noxacusis," to coin a term.…”
mentioning
confidence: 99%